(untitled) (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to examine the multiple mediating effect of growth mindset, grit and hope on the effect of employment stress on happiness among 364 college students in Korea. Method/Statistical Analysis: The data for the study were collected from 364 university students by using survey method. For the statistical analysis, frequency analysis, reliability analysis, correlation analysis and mediation analysis all were performed using SPSS Win.24.0 and PROCESS macro for SPSS version 3.2. Findings: The results of the study are as follows. First, it is noted that the Pearson correlation analysis showed that happiness had a negative correlation with employment stress, and there was a significant positive correlation among growth mindset, grit and hope. Broadly speaking, employment stress showed a significant negative correlation with happiness, growth mindset, grit, and hope. Second, as a result of the PROCESS macro analysis, employment stress affects growth mindset, hope and happiness, and growth mindset has a positive effect on grit, hope and happiness. To this end, it is noted that grit has a positive effect on hope, happiness, and hope has a positive influence on happiness. Third, there was a multiple mediation effect of growth mindset, grit and hope in the identified relationship between employment stress and happiness. Improvements/Applications: This result will be utilized as a new model in which growth mindset, grit and hope mediate the job-seeking stress of university students in the process of affecting happiness in the Korean society where the employment crisis is at serious proportions.